Physics and politics in revolutionary Russia - Josephson, Paul R. (Berkeley : University of California Press, 1991)
Aided by personal documents and institutional archives that were closed for decades, this book recounts the development of physics--or, more aptly, science under stress--in Soviet Russia up to World War II. Focusing on Leningrad, center of Soviet physics until the late 1930s, Josephson discusses the impact of scientific, cultural, and political revolution on physicists' research and professional aspirations. Political and social revolution in Russia threatened to confound the scientific revolution. Physicists eager to investigate new concepts of space, energy, light, and motion were forced to accommodate dialectical materialism and subordinate their interests to those of the state. They ultimately faced Stalinist purges and the shift of physics leadership to Moscow. This account of scientists cut off from their Western colleagues reveals a little-known part of the history of modern physics.
Frontmatter -- Contents -- Illustrations -- Acronyms and Abbreviations -- Plates -- Acknowledgments -- Introduction -- 1. The Politics of Tsarist Physics -- 2. The Russian Revolution and the Search for a National Science Policy -- 3. The Russian Association of Physicists and the Founding of the Leningrad Physico-Technical Institute -- 4. The Flowering of Soviet Physics: National Achievements and International Aspirations During the New Economic Policy -- 5. Physics During the First Five-Year Plan: Industrialization and Stalinist Science Policy -- 6. Cultural Revolution and the Natural Sciences -- 7. Theoretical Physics: Dramatis Personae -- 8. Theoretical Physics: Dialectical Materialism and Philosophical Disputes -- 9. The Great Terror and the Assault on the Leningrad Physics Community -- Epilogue -- Appendix A: The History and Politics of Soviet Physics -- Appendix B: The Leningrad Physico-Technical Institute -- Appendix C: Publication -- Notes -- Selected Bibliography -- Index
Includes bibliographical references (pages 397-412) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Physics -- Soviet Union -- History -- 20th century; Physics -- Research -- Soviet Union -- History; Physics -- Political aspects -- Soviet Union -- History; Science and state -- Soviet Union -- History -- 20th century; Science -- Political aspects -- Soviet Union -- History; Physique -- URSS -- Histoire -- 20e siècle.; Physique -- Recherche -- URSS -- Histoire; Physique -- Aspect politique -- URSS -- Histoire; Politique scientifique et technique -- URSS -- Histoire -- 20e siècle.; Sciences -- Aspect politique -- URSS -- Histoire; SCIENCE -- Philosophy & Social Aspects; SCIENCE / General; Physics; Physics -- Research; Science and state; Science -- Political aspects; Soviet Union; Russische Revolutie; Natuurkunde; Sovjet-Unie.; Physics; Physical Sciences & Mathematics; Physics - General; 1900-1999; History